Makna Simbolis Ornamen pada Bangunan Pagoda Avalokitervara Buddhagaya Watugong Semarang - Eva Nurhida Maulidha; Lubnaya Nabigha (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study aims to identify the types of ornaments on the Avalokitesvara Pagoda Watugong Semarang, explain their symbolic meaning in the context of Buddhist teachings, and analyze how the ornaments reflect Buddhist architectural philosophy and spiritual values. The results of the study show that this pagoda is decorated with a variety of ornaments, such as reliefs of dragons, hong birds, humans, animals, Chinese writing, amulets of the eight gods, and pineapple ornaments. Each ornament has a deep symbolic meaning, reflecting values such as love, wisdom, and balance in life. The dragon relief symbolizes power and spirituality, the hong bird represents luck and peace, while the Chinese writing and the amulet of the eight gods symbolize blessings and good fortune in life. The ornaments also reflect the Buddhist architectural philosophy that emphasizes harmony between humans, nature, and spirituality, with the towering building design as a symbol of aspiration towards spiritual perfection. Apart from being a place of worship, this pagoda also functions as an interfaith meditative space, affirming the values of tolerance and harmony. This study concludes that the ornaments on the Avalokitesvara Watugong Pagoda are not only decorative elements, but also full of philosophical and spiritual meanings that enrich cultural values and strengthen tolerance. It is recommended to improve the preservation of ornaments, the development of education, and further research to explore the deep meaning of the existing reliefs.